2017
DOI: 10.5377/payds.v6i0.5716
|View full text |Cite
|
Sign up to set email alerts
|

Siembra directa: una alternativa para mejorar la sustentabilidad del cultivo de arroz (Oryza sativa L.) en el Perú

Abstract: En el Perú, el sistema de siembra de arroz al trasplante tiene altos costos de producción, y los riegos de inundación contribuyen a la emisión de metano. Existen otros sistemas de producción que mejorarían la sustentabilidad del cultivo. Este estudio tuvo como objetivo comparar los sistemas de siembra directa en seco (en hileras y al voleo) versus los sistemas de trasplante (sistema intensivo de cultivar arroz (SICA), trasplante en hileras y trasplante convencional), en la productividad del cultivar IR-43, y s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…Still, the farmers with the highest GHG efficiency were able to maintain yields while experiencing drying events, which is consistent with studies showing that alternate wetting and drying (AWD) can significantly reduce methane emissions without yield loss (Linquist et al, 2015;Xu et al, 2015;Liang et al, 2016;Setyanto et al, 2018). Recent research (Pando et al, 2017) has demonstrated AWD and direct seeding as successful options in northern Peru, but changes in water distribution and suitable cultivars that tolerate drying periods are needed. Extension efforts demonstrating effective AWD and efficient weed management could change the perception that drying events are harmful for the crop.…”
Section: Resource Use Efficiencies and Prospects For Sustainable Intensificationsupporting
confidence: 78%
See 1 more Smart Citation
“…Still, the farmers with the highest GHG efficiency were able to maintain yields while experiencing drying events, which is consistent with studies showing that alternate wetting and drying (AWD) can significantly reduce methane emissions without yield loss (Linquist et al, 2015;Xu et al, 2015;Liang et al, 2016;Setyanto et al, 2018). Recent research (Pando et al, 2017) has demonstrated AWD and direct seeding as successful options in northern Peru, but changes in water distribution and suitable cultivars that tolerate drying periods are needed. Extension efforts demonstrating effective AWD and efficient weed management could change the perception that drying events are harmful for the crop.…”
Section: Resource Use Efficiencies and Prospects For Sustainable Intensificationsupporting
confidence: 78%
“…Farmers discussed their reluctance to try direct seeding due to worries about water scheduling and increased weed pressure. Recent research has highlighted the benefits of direct seeding in Peru (Pando et al, 2017), but there is a need to increase extension opportunities to inform farmers about specific production or post-production options that could generate higher profits.…”
Section: Profitability and Decision-makingmentioning
confidence: 99%